Asymmetric response of Investor sentiment to Economic Policy Uncertainty, interest rates and oil price uncertainty: Evidence from OECD countries - Hassen Guenich; Khalfaoui Hamdi; Néjib Chouaibi (Cogent Economics & Finance, 2022)
The question of the economic policy uncertainty, interest rate and oil price volatility and their effects on investor sentiment is rarely addressed by the literature. Thus, we are motivated to provide new insights into the study of these effects based on asymmetric analysis. Our empirical study is based on the monthly frequency of 22 OECD countries and ranges from January 2000 to June 2021. Using the Nonlinear Autoregressive Distributed Lag (NARDL) panel model, we find that economic policy uncertainty, interest rate and oil price uncertainty have disproportionately asymmetric effects on OECD investor sentiment in the short and long run. Indeed, when occurring volatility of these variables, investors will certainly adopt, according to their sentiments, different directions and strategies of investment decision-making.
Keywords: E44; E71; G41; Q43; 330; asymmetric relationships; Economic policy uncertainty; interest rate; investor sentiment; NARDL; oil price volatility